Artificial intelligence-incorporated membrane fouling prediction for membrane-based processes in the past 20 years: A critical review. (1st June 2022) - Niu, Chengxin; Li, Xuesong; Dai, Ruobin; Wang, Zhiwei
Highlights: Recent advances in artificial intelligence for predicting fouling are presented. Working principles of AI technologies for membrane fouling prediction are discussed. Comparisons of the inputs, outputs, and accuracy of AI approaches are conducted. Future research efforts are highlighted for AI technologies in predicting membrane fouling. Abstract: Membrane fouling is one of major obstacles in the application of membrane technologies. Accurately predicting or simulating membrane fouling behaviours is of great significance to elucidate the fouling mechanisms and develop effective measures to control fouling. Although mechanistic/mathematical models have been widely used for predicting membrane fouling, they still suffer from low accuracy and poor sensitivity. To overcome the limitations of conventional mathematical models, artificial intelligence (AI)-based techniques have been proposed as powerful approaches to predict membrane filtration performance and fouling behaviour. This work aims to present a state-of-the-art review on the advances in AI algorithms (e.g., artificial neural networks, fuzzy logic, genetic programming, support vector machines and search algorithms) for prediction of membrane fouling. The working principles of different AI techniques and their applications for prediction of membrane fouling in different membrane-based processes are discussed in detail. Furthermore, comparisons of the inputs, outputs, and accuracy of different AI approaches for membrane fouling prediction have been conducted based on the literature database. Future research efforts are further highlighted for AI-based techniques aiming for a more accurate prediction of membrane fouling and the optimization of the operation in membrane-based processes. Graphical Abstract: Image, graphical abstract